Inovasi Strategi Pembelajaran PAI Dalam Meningkatkan Mutu Pendidikan PAI - Rohmah, Noer (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Islamic education has important role in the human life that based on Five Basic of the State, because religion is motivation of life and the important tool of development and self-control. Therefore, religion should be known, understood, and practiced by humans in order to be fully human in life.Nowadays, learning of Islamic Education in the school is more focused on formal and memorization (verbal) and theoretical things, not focused on the purpose so forget about the ability to control themselves and how to buildfaith. Because of it, teachers need to do various innovation in the process of implementation strategy of Islamic Education in the school, in order to improve quality of Islamic Religion that signed by various change both of cognitive, affective, and psychomotor.Keywords: Innovation of Learning Strategy of Islamic Education, Quality of Islamic Education.